South American Cucurbit Fruit Fly, Anastrepha grandis (Macquart) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr. (EDIS, 2004)
Anastrepha grandis (Macquart) (1846: 227), which exists in several South American countries and possibly Panama, attacks watermelon and other fruits of the family Cucurbitaceae. Once a pest of minor to moderate importance generally, in recent years it has become a rather important pest. The pest status differs in each country and has changed in the last decade. This species would seem to be potentially of economic importance in Florida and southern Texas should it ever be introduced there. It has been intercepted in the United States in pumpkin from Argentina and Brazil, and one adult was found in banana debris from Panama. This document is EENY-205 (originally published as DPI Entomology Circular 334), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2001.